ChemInform Abstract: Highly Enantioselective Construction of 3‐Hydroxy Oxindoles Through a Decarboxylative Aldol Addition of Trifluoromethyl α‐Fluorinated gem‐Diols to N‐Benzyl Isatins. Issue 41 (19th September 2013) - Saidalimu, Ibrayim; Fang, Xiang; He, Xiao‐Peng; Liang, Jing; Yang, Xueyan; Wu, Fanhong
Abstract An organocatalytic asymmetric direct aldol addition reaction of gem‐diols to isatins is developed.